A Scientometric Study of Contributions by African-affiliated Authors to Engineering Education Research Journals 2004-2023 - Williams, Bill; Valentine , Andrew (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Engineering education research has grown considerably as a field of inquiry over the last 20 years, particularly in the US, Europe and Australia. This study applies a scientometric approach to the contributions from Africa-affiliated authors to 19 engineering education research journals, 2004 - 2023. In the 385 journal articles published, South Africa was notably the most prolific contributor with 147 articles, followed by Egypt, Nigeria, Botswana and Tunisia. While this research output is comparable with that of other regions in the Global South, it remains significantly lower than that of regions in the Global North. It was noted that the annual average article output was 11 in the period up to 2015 whereas from that year onwards it rose to 28 per annum. Authors from South Africa and Botswana tended to co-author with colleagues from the US whereas those from Tunisia partnered with Saudi Arabian co-authors. The most common keywords were students, engineering education and E-learning. Three engineering education research centres were identified, two in South Africa and one in Nigeria. We believe that these findings can serve as a useful baseline to allow scholars to monitor the evolution of research in engineering education by African educators over future decades.